Ètude et simulation du système MIMO à Formation de faisceaux - صفاء, رزقه; هناء, يحي (University Of El Oued, 2020)
Future mobile networks will use both low and high frequencies, but they are expected to deliver their highest speeds on millimeter waves. Fortunately, the shorter wavelength of a millimeter wave signal allows for greater antenna gain when using an antenna array with a large number of antenna elements (MIMO). It is known that the existing point-to-point millimeter wave communication system with a large antenna array can achieve multigigabit data rates at a line-of-sight distance of a few kilometers. However, the fixed narrow beam offers limited geographic coverage. In general, the beamforming system can provide higher transmitted power and better beamforming flexibility. MIMO Beamforming techniques can offer high antenna array gain, anti-interference, better signal coverage and high spectral efficiency for future mobile networks with millimeter wave cellular communication. The main goal of this work is to study and simulate the types of adaptive beamfoming using multiple transmit and receive (MIMO) antennas, where a comparison of these types has been made. ستستخدم شبكات الهاتف المحمول المستقبلية كلاً من الترددات المنخفضة والعالية ، لكن من المتوقع أن تقدم أعلى سرعاتها على موجات المليمتر. لحسن الحظ ، يسمح الطول الموجي الأقصر لإشارة الموجة المليمترية بكسب أكبر للهوائي عند استخدام صفيف هوائي به عدد كبير من عناصر الهوائي (MIMO). من المعروف أن نظام اتصال الموجات المليمترية الموجود من نقطة إلى نقطة مع صفيف هوائي كبير يمكن أن يحقق معدلات بيانات متعددة الجيجابايت على مسافة خط رؤية تبلغ بضعة كيلومترات. ومع ذلك ، فإن الحزمة الضيقة الثابتة توفر تغطية جغرافية محدودة. بشكل عام ، يمكن أن يوفر نظام تشكيل الحزم قدرة إرسال أعلى ومرونة أفضل في تشكيل الحزمة. يمكن أن توفر تقنيات MIMO Formation des faisceaux كسبًا عاليًا لصفيف الهوائي ، ومقاومة للتداخل ، وتغطية أفضل للإشارة ، وكفاءة طيفية عالية لشبكات المحمول المستقبلية مع الاتصالات الخلوية بموجة ملليمتر. الهدف الرئيسي من هذا العمل هو دراسة ومحاكاة أنواع إرسال الحزمة التكيفية باستخدام هوائيات متعددة للإرسال والاستقبال (MIMO) ، حيث تم إجراء مقارنة بين هذه الأنواع.
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: MIMO, Beamforming, MVDR, LCMV, LMS, RLS.; MIMO, تشكيل الشعاع, MVDR, LCMV, LMS, RLS :